2014
DOI: 10.1080/03004430.2014.944907
|View full text |Cite
|
Sign up to set email alerts
|

Applying Pleck's model of paternal involvement to the study of preschool attachment quality: a proof of concept study

Abstract: Recent re-conceptualisation of paternal involvement (Pleck, J. H. (2010). Paternal involvement: Revised conceptualization and theoretical linkages with child outcomes. In M. Lamb (Ed.), The role of the father in child development (5th ed., pp. 67-107). London: Wiley), while proving fruitful, has yet to be applied to investigations into what extent a father's level of involvement may affect childpeer interactions in the preschool age range, over and above the effects of motherchild attachment quality and socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…It is thus important to consider mothers' perceptions of paternal involvement with childcare responsibilities as a dimension of parenting that can account for maternal mental health and well-being, as shown in the present study and previous work ( 12 , 16 ), as well as a notable contributor to children's emotional and behavioral outcomes ( 45 48 ). A recent study has demonstrated, with longitudinal data from pregnancy to child's age of 24 months, that changes in fathers' perception of the quality of their marriage is an important factor in accounting for coparenting quality ( 49 ).…”
Section: Discussionmentioning
confidence: 80%
“…It is thus important to consider mothers' perceptions of paternal involvement with childcare responsibilities as a dimension of parenting that can account for maternal mental health and well-being, as shown in the present study and previous work ( 12 , 16 ), as well as a notable contributor to children's emotional and behavioral outcomes ( 45 48 ). A recent study has demonstrated, with longitudinal data from pregnancy to child's age of 24 months, that changes in fathers' perception of the quality of their marriage is an important factor in accounting for coparenting quality ( 49 ).…”
Section: Discussionmentioning
confidence: 80%
“…For example, it has been found that fathers and mothers interact with their young children with equal sensitivity (Notaro and Volling 1999). This is why some researchers claim that at present there are more similarities than dissimilarities in how mothers and fathers interact with their children (Kennedy et al 2015; Lamb 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, strong relationships with caregivers constitute a significant protective factor. The importance of father involvement in youth adjustment is well demonstrated in the literature; increased father involvement is associated with improved behavior regulation (Easterbrooks, Raskin, & McBrian, 2014) and academic outcomes (Jeynes, 2015), and reductions in externalizing behaviors (Kennedy, Betts, Dunn, Sonuga-Barke, & Underwood, 2015). These associations may result from enhanced attachment security (Brown, McBride, Shin, & Bost, 2007), interaction characteristics unique to father–child relationships, as paternal advice-giving content and style is predictive of a child's social competence above and beyond the mother's advice (McDowell, Parke, & Wang, 2003), and/or emotion regulation strategies that fathers convey either through modeling or direct teaching that youth may incorporate into their own self-regulation (Dubowitz et al, 2001).…”
Section: Ecological Model Of Externalizing Behaviormentioning
confidence: 98%